Muscle vibration: Different effects on transcranial magnetic and electrical stimulation - Kossev, Andon; Siggelkow, Sabine; Schubert, Margot; Wohlfarth, Kai; Dengler, Reinhard (Muscle & nerve, 1999)
Transcranial magnetic stimulation (TMS) and transcranial electrical stimulation (TES) were applied before and 3 s after onset of vibration (0.5 mm, 80 Hz) of the right extensor carpi radialis muscle in 5 healthy subjects. Vibration induced significant augmentation and latency shortening of motor evoked potentials elicited by TMS, but not TES. This provides evidence for an involvement of cortical mechanisms by muscle vibration in the augmentation of MEPs following TMS. © 1999 John Wiley & Sons, Inc. Muscle Nerve 22: 946–948, 1999